2003
DOI: 10.1136/ijgc-00009577-200311000-00009
|View full text |Cite
|
Sign up to set email alerts
|

CYP1A1 polymorphism and risk of gynecological malignancy in Japan

Abstract: The incidence of endometrial cancer and ovarian cancer in Japan has been increasing in recent years. Results of epidemiologic studies suggest that the onset and multiplication of these cancers are associated with estrogen. Estrogens are metabolized by cytochrome P450 1A1 (CYP1A1) and converted into catecholestrogens, which are carcinogens. CYP1A1 has several polymorphisms, the major one being T6235C transition in the non-coding 3′-flanking region (MspI polymorphism), and another being A4889G transition in exon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 16 publications
1
21
2
Order By: Relevance
“…Moreover, the CYP1A1 Ile462Val polymorphism has shown to be a risk factor of cervical cancer in the Chinese population (Huang et al, 2006;Geng et al, 2010;Shi et al, 2011). On contrary to present findings, studies conducted in Polish and Japanese population did not find CYP1A1 Ile462Val polymorphism as an increased risk for cervical cancer (Sugawara et al, 2003;Roszak et al, 2014). Thus, it is obvious that cancer development may arise due to genetic polymorphism in metabolic enzyme.…”
Section: Discussioncontrasting
confidence: 66%
“…Moreover, the CYP1A1 Ile462Val polymorphism has shown to be a risk factor of cervical cancer in the Chinese population (Huang et al, 2006;Geng et al, 2010;Shi et al, 2011). On contrary to present findings, studies conducted in Polish and Japanese population did not find CYP1A1 Ile462Val polymorphism as an increased risk for cervical cancer (Sugawara et al, 2003;Roszak et al, 2014). Thus, it is obvious that cancer development may arise due to genetic polymorphism in metabolic enzyme.…”
Section: Discussioncontrasting
confidence: 66%
“…However, no significant relation between CYP1A1 polymorphisms and gynaecological malignancies could be detected in other studies [45,46].…”
Section: Cyp1a1contrasting
confidence: 52%
“…The findings of previous studies investigating the association between CYP1A1 polymorphisms and endometrial cancer risk have been inconsistent [14][15][16][17][18][19][20] (Table 5). Esteller et al [14,15] conducted a small case-control study (n = 80 cases and 60 controls) and observed a statistically significant 3-to 4-fold increase in risk associated with carriage of the MspI allele and the Val462 allele [14], along with a 6-fold increase in risk associated with carriage of the Asn461 allele [15].…”
Section: Discussionmentioning
confidence: 91%
“…Contrary to the findings of Esteller et al [14,15], Doherty observed a statistically significant decrease in risk associated with the carriage of at least one MspI or Val462 allele and no decrease in risk was observed associated with the Asn461 allele. A Japanese case-control study and a Polish case-control study concluded no significant associations with the MspI, Ile462Val, and Thr461Asn polymorphisms and endometrial cancer risk [18,20]. Recently, a large population-based case-control study of 502 cases and 1,326 age-and race-matched controls concluded that there was a significant association with genotypes that contained any Val462 allele as compared with genotypes without a Val462 allele [17].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation